Diagnostic Dilemma of Leukemoid Reaction in Pediatric Pyoderma Gangrenosum - Snehal Umesh Chopade; Siddhi B. Chikhalkar; Shreya Singh; Priyanka R. Kute; Pooja Manohar Golwad; Pramod Dhanraj Kamble; Vidya Kharka (Indian Journal of Paediatric Dermatology)
Pyoderma gangrenosum (PG) is a chronic neutrophilic dermatological disorder mostly seen in adults. The incidence of PG is only 4% in the pediatric age group. We present a case of an 11-year-old boy who had a painful ulcer with constitutional symptoms and a hematological leukemoid reaction, which could mislead the clinician toward an infective etiology. In such a dilemma, our case showed successful recovery with systemic steroids and colchicine confirming the diagnosis of PG.